Impact of Rural - Urban Labour Migration on Education of Left Behind Children : Evidence from Rural India - Agasty, Mahendra P. (Arthshastra Indian Journal of Economics & Research, 2016)
A number of studies have shown that adult male migration occurs from rural areas for harnessing better employment opportunities and assists in achieving financial stability for a migrant family, but research has showed that the absence of parents can be detrimental to a child's social and psychological development. Migration of adult household members can affect the education of children who are left behind in several ways. On the basis of a sample survey of 200 households spread over six villages in three blocks of Kendrapara district in Odisha, India, this paper analyzed the educational status of the children left behind. The results indicated that migration mattered for the education of children. It is evident from the study that enrolment-wise, children of migrant households were ahead of children of returned migrant and non-migrant households; however, in case of school attendance, continuation in education, and educational attainment, they lagged behind children in the latter two categories of households.